Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

Reaction of huisgen zwitterion with 1,2-benzoquinones and isatins: expeditious synthesis of dihydro-1,2,3-benzoxadiazoles and spirooxadiazolines - Nair, Vijay; Biju, Akkattu T.; Vinod, A. V.; Eringathodi, Suresh (Organic Letters, 2005)
The zwitterionic intermediate generated from dialkyl azodicarboxylate and triphenylphosphine on reaction with 3-methoxy-1,2-benzoquinones afforded dihydro-1,2,3-benzoxadiazoles. N-Substituted isatins furnished spirooxadiazolines under similar conditions.

DMAP-catalyzed reaction of beta-ketoesters and dimethyl acetylenedicarboxylate: an efficient synthesis of polysubstituted benzenes and biaryls - Nair, Vijay; Vidya, N.; Biju, Akkattu T.; Deepthi, Ani B.; Abhilash, K. G.; Eringathodi, Suresh (Tetrahedron, 2006)
A DMAP catalyzed tandem addition–cyclization–dehydration sequence involving dimethyl acetylenedicarboxylate and β-ketoesters leading to polysubstituted benzene/biaryl derivatives is presented.

Novel synthesis of highly functionalized pyrazolines and pyrazoles by triphenylphosphine mediated reaction of dialkyl azodicarboxylate with allenic esters - Nair, Vijay; Biju, Akkattu T.; Mohanan, Kishor; Eringathodi, Suresh (Organic Letters, 2006)
Reaction of the Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with allenic esters affords highly functionalized pyrazolines and pyrazoles. The crystal structure of pyrazoline derivative 7a showed extensive C−H···O interactions. Pyrazole formation proceeds via a novel nitrogen to carbon migration of the carboalkoxy group.

Efficient higher-order cycloaddition reactions of 8,8-dicyanoheptafulvenes with dienes - Nair, Vijay; Gopalakrishnan Abhilash, K.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2007)
The cycloaddition reactions of 8,8-dicyanoheptafulvene with electron-rich dienes afforded the higher order cycloaddition products in excellent yields. With cyclic dienes as well as dimethoxybutadiene the [8+2] adducts were obtained exclusively. With methyl- and dimethylbutadienes the [6+4] adducts were the only products isolated.
Keywords: cycloadditions - bicyclic compounds - polycycles - dicyanoheptafulvene - tetrahydroazulenes

Novel reaction of the “huisgen zwitterion” with chalcones and dienones: an efficient strategy for the synthesis of pyrazoline and pyrazolopyridazine derivatives - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Eringathodi, Suresh (Angewandte Chemie-International Edition, 2007)
Two unexpected transformations: The reaction of the Huisgen zwitterion derived from triphenylphosphane and diisopropyl azodicarboxylate (DIAD) with chalcones affords functionalized pyrazolines. In contrast, the reaction with dienones affords pyrazolopyridazines, presumably by Diels–Alder reaction of the initially formed pyrazoline with excess DIAD (see scheme).
Keywords: chalcones; nitrogen heterocycles; pyrazolines; synthetic methods; zwitterions

Reaction of tpp-azodicarboxylate zwitterions and aldehydes: unprecedented synthesis of acyl carbamates - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Tetrahedron Letters, 2007)
An efficient synthesis of acyl carbamates from aryl aldehydes by the reaction of triphenylphosphine and dialkyl azoesters is described.

Reaction of huisgen zwitterion with diaryl ketones leading to the facile synthesis of mono- and bis(alkoxycarbonyl)hydrazones - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2008)
The Huisgen zwitterion, generated from triphenylphosphine and dialkyl azodicarboxylates, afforded upon reaction with diaryl ketones both mono- and bis(alkoxycarbonyl)hydrazones, depending on the reaction conditions.

Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate